Sedation – hopes and dangers - Stachowiak, Andrzej; Mrówczyńska, Ewa (Medycyna Paliatywna/Palliative Medicine, 2011)
The aim of palliative care is to provide the patients with appropriate comfort of life and comfort of dying. As the terminal disease advances, the suffering connected with refractory and unresponsive to intensive treatment symptoms may often escalate in patients. If, despite using all the available methods of symptomatic treatment, the symptoms are not relieved, decision on applying palliative sedation is made in agreement with the patient and his or her family. It lies in the administration of sedatives, as an addition to symptomatic medication previously used in the patient. It is referred to as the last-line treatment, whose aim is the controlled limitation of consciousness, proportionally to the need of alleviation of suffering which is difficult to control otherwise. This form of a last resort treatment should not hasten death and should be ethically accepted. From a moral point of view, sedation should not be treated equally with euthanasia, which palliative care strongly opposes. Sedation in palliative care is a part of treatment and its aim is to relieve suffering and not hasten death in the patient. The undeniable risk of palliative sedation is, which is reported in some European countries, its unethical and illegal use for administering euthanasia. A controversial issue is still the use of palliative sedation for relieving burdensome psycho-existential suffering. The current studies show that specialists in Poland should create proper guidelines concerning practical use of therapeutic sedation in palliative care of both cancer patients and non-cancer ones.